(untitled) (قضايا سياسية, 2025)
The research aims to study and understand the role of the Russian military establishment in shaping Russian security policy under current President Vladimir Putin. This policy is a comprehensive, long-term vision for confronting existing and potential threats to national security. This vision encompasses the state's political, military, economic, and social security, taking into account national political realities at the regional and global levels, and not excluding geopolitical considerations. This vision enables the identification of all forms of threats to national security, assessing their likelihood and severity, and determining options to contain these threats, either by limiting their impact by neutralizing them and removing them from the circle of confrontation, or by confronting them directly or indirectly. The study then develops the necessary policies, plans, and executive programs to address them, achieving the highest levels of state security, and the extent to which this can be applied exclusively to Russian strategy، The study employs a historical-systematic approach and a descriptive-analytical approach.